Bacteria and Boar Semen Storage: Progress and Challenges - María José Contreras; Kattia Núñez-Montero; Pablo Bruna; Matías García; Karla Leal; Leticia Barrientos; Helga Weber (MDPI AG, 2022)
Porcine breeding today is based on artificial insemination with chilled semen. This is stored at 5 °C with antibiotic supplementation to avoid bacteriospermia. There are many negative consequences on sperm quality and functionality as a result of bacterial contamination, as well as on the health of the sow. Nowadays, various techniques are being developed to reduce the indiscriminate use of antibiotics and thus avoid the generation of antibiotic resistance genes. This review aims to inform about the bacterial contamination consequences of storing liquid semen from boar and to provide an update on current methods and alternatives to antibiotic use in cold storage.